ANALISIS EFEKTIFITAS PROGRAM BANTUAN LANGSUNG TUNAI DALAM MENANGGULANGI KEMISKINAN DI KOTA MATARAM - Jeriah, Ainul; Nurfadilah, Siti (JURNAL ILMIAH DETUBUYA, 2024)
This study evaluates how effective the Direct Cash Assistance (BLT) Program is in addressing poverty in Mataram City. This study focuses on the impact of BLT on the economic, social, and psychological conditions of recipients, and assesses technical obstacles that arise in the implementation of the program, such as mistargeting, lack of supervision, and suboptimal use of funds. Using qualitative and quantitative approaches, data were obtained from field observations, interviews, and official documents. The findings of this study indicate that although BLT provides short-term benefits in maintaining purchasing power and a sense of security for the community, this program has not succeeded in creating sustainable economic independence without the support of education and empowerment. This study recommends that BLT be integrated with economic empowerment programs and increased accountability and routine evaluation as a strategy to strengthen poverty alleviation programs.